Simple method to determine the effective conductivity of porous media saturated with a phase changing liquid - Wolfgang Leidenfrost and Dieter Lindemann (International journal of refrigeration, 1988)
Effective thermal conductivities of porous materials saturated with phase changing liquids, needed for the proper design of, for example, storage type heat exchangers or rectification columns, cannot be computed reliably from models available in the literature. To overcome this drawback a very simple measurement technique was conceived. It can easily be applied by using inexpensive and easy to build test cells. Measurements of heat flows or temperature distributions are not needed. The only requirement is that heat transfer surfaces in contact with thet substance can be changed and maintained at a desired temperature for freezing or melting the phase change material (PCM). Effective thermal conductivity data are listed for different porous metals of different shape and porosity, and saturated with water (ice). It can be assumed that these data are accurate because the thermal conductivities of pure solid or liquid PCM were measured accurately. Some quality criteria are introduced which will be helpful in the proper desin of latent energy stores. © 1988.
Keywords: conductivité thermique; heat transfer; milieux poreux; porous media; thermal conductivity; transfert de chaleur